2007
DOI: 10.1002/jor.20395
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short‐term treatment with alendronate on ulnar bone adaptation to cyclic fatigue loading in rats

Abstract: Targeted remodeling of fatigue-injured bone involves activation of osteoclastic resorption followed by local bone formation by osteoblasts. We studied the effect of parenteral alendronate (ALN) on bone adaptation to cyclic fatigue. The ulnae of 140 rats were cyclically loaded unilaterally until 40% loss of stiffness developed. We used eight treatment groups: (1) baseline control; (2) vehicle (sterile saline) and (3) alendronate before fatigue, no adaptation (Pre-VEH, Pre-ALN, respectively); (4) vehicle and (5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…(65) Animal studies using repetitive ulnar loading in combination with BP treatment also show that prior alendronate treatment does not protect against a fatigue-related reduction in mechanical properties. (66) However, prior alendronate treatment did eliminate the adaptive remodeling response, suggesting that BP treatment could impair the healing response to a stress fracture. Therefore, it is possible that in the case of a developing stress fracture, reduction of bone remodeling would prevent or delay the repair of the stress reaction without suppressing the appearance of a periosteal callus and that this may result eventually in consolidation of the damage and a complete fracture of the stressed site.…”
Section: Insights Into the Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…(65) Animal studies using repetitive ulnar loading in combination with BP treatment also show that prior alendronate treatment does not protect against a fatigue-related reduction in mechanical properties. (66) However, prior alendronate treatment did eliminate the adaptive remodeling response, suggesting that BP treatment could impair the healing response to a stress fracture. Therefore, it is possible that in the case of a developing stress fracture, reduction of bone remodeling would prevent or delay the repair of the stress reaction without suppressing the appearance of a periosteal callus and that this may result eventually in consolidation of the damage and a complete fracture of the stressed site.…”
Section: Insights Into the Pathogenesis Of Atypical Femoral Fracturesmentioning
confidence: 99%
“…Several different animal models have been used to study the pathogenesis of stress fractures. Existing rodent models (3,4,66) may not be appropriate because of their lack of haversian remodeling, but attempts should be made to adapt fatigueloading techniques that have been developed in rodents to larger animals. Nonhuman primates would be acceptable but are expensive.…”
Section: Key Research Questionsmentioning
confidence: 99%
“…The use of bisphosphonates has been proposed as a preventive measure against stress fractures. 8,9 However a trial in army recruits failed to show any preventive efficacy of risedronate therapy. 8 Treatment with pamidronate was reported to produce a beneficial effect in clinical stress fractures in young athletes, 10 but this study only had small numbers of cases.…”
mentioning
confidence: 99%
“…The woven bone response was not affected by alendronate treatment initiated before or after loading. 9 These effects were, however, only examined at a maximum of 2 weeks following loading. Another study using the rat ulna loading model demonstrated that treatment with aledronate did not affect resorption space area, repaired crack length or woven bone area at 2 and 4 weeks after stress fracture creation but that mineral apposition rate and bone formation rate were decreased at 4 weeks after loading.…”
mentioning
confidence: 99%
See 1 more Smart Citation